Circulação e intercâmbio de plantas e conhecimentos fitomedicinais na fronteira franco-brasileira - Marc-Alexandre Tareau; Lucie Dejouhanet; Marianne Palisse; Guillaume Odonne (Confins)
Pharmacopoeias are, like any kind of cultural production, living and dynamic objects that constantly change and reinvent themselves, throughout continuous contacts and exchanges between different social groups. Medicinal plants are “biocultural objects” (Pordié, 2002) as well, because of the richness and the complexity of relationships that societies develop with them. In French Guiana, especially in its cross-border areas, cultural interactions are usual. Plants and knowledge about their uses circulate among communities, contributing to a permanent renewal and a continuous hybridation of herbal medicines. These material and immaterial flows form the cultural reality of cross-border areas on the Guiana Shield. This paper focuses on the border between French Guiana and Brazil, which was made tangible by the Oyapock River. Based on interviews conducted in the French border town of Saint-Georges-de-l’Oyapock, it proposes an exploratory description of ethnobotanical flows in this cross-border context. It lists the medicinal plants used in Saint-Georges, analyses the diffusion of associated knowledge between the different communities and highlights the circulations of plants and of related medicinal knowledge in this transfrontier area. This research is one part of a larger study on biocultural circulations at the scale of French Guiana and its neighbours.